2020
DOI: 10.3390/w12061716
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Study on Freshwater Ecosystem Health of Lancang River Basin in Xishuangbanna of China

Abstract: The Lancang-Mekong River significantly affects the livelihood of residents in the basin as well as the lives of people in other regions of the world in terms of great development potential and its economic and ecological values. In the meanwhile, the river attracts the attention of countries in the basin and the international community because it raises potential for international conflicts. The Lancang-Mekong River leaves China from Xishuangbanna and the ecosystem status in Xishuangbanna constitutes one of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…While these scenarios are simplistic and applied uniformly to all dams, they provide a useful envelope for estimating the range of potential impacts from dramatically changing dam operation rules. Leveraging an established methodology that isolates and scores the ecosystem risks and benefits of changing water landscapes 33 , 37 , 38 , we then used the social-ecological framework of the Freshwater Health Index 32 to compare the results of these scenarios and their relative impacts on key indicators of ecological health and human well-being.…”
Section: Resultsmentioning
confidence: 99%
“…While these scenarios are simplistic and applied uniformly to all dams, they provide a useful envelope for estimating the range of potential impacts from dramatically changing dam operation rules. Leveraging an established methodology that isolates and scores the ecosystem risks and benefits of changing water landscapes 33 , 37 , 38 , we then used the social-ecological framework of the Freshwater Health Index 32 to compare the results of these scenarios and their relative impacts on key indicators of ecological health and human well-being.…”
Section: Resultsmentioning
confidence: 99%
“…However, with few exceptions, such as the European Union's Water Framework Directive, decision-makers are at an early stage in developing and integrating ecosystem services into water resource management. In apply this indicator framework under FHI (basins from Asia, Africa, and Latin America) we have found that most stakeholders, whilst familiar with the concept of water ecosystem services, have considered them less often than the bio-physical or governance aspects of water management (Vollmer et al 2018;Bezerra et al 2021;Souter et al 2020;Wen et al 2020). Furthermore, the need for monitoring and management of water ecosystem services is not yet legislated in many jurisdictions (cf Liu et al 2019).…”
Section: Focusing On Delivery Of Water Ecosystem Services As a Starting Pointmentioning
confidence: 99%
“…(Vollmer et al 2018;Souter et al 2020;Wen et al 2020;Bezerra et al 2021). It can incorporate both modeled and measured data, of a variety of variable types, collected at different frequencies and spatial units (Table…”
mentioning
confidence: 99%
“…The FHI frames freshwater ecosystems as dynamic social-ecological networks, with linkages and feedbacks that reveal human water needs and the ecological effects of using fresh water in a watershed. This focus on freshwater ecosystem health engages stakeholders and decision-makers (Vollmer et al 2020;Souter et al 2020;Wen et al, 2020). The FHI incorporates both supply and demand for water-related ecosystem services, which diagnoses freshwater health for land and water resource managers and provides a mechanism for evaluating tradeoffs.…”
Section: Introductionmentioning
confidence: 99%